FAMILY NURSING THE EFFECTIVENESS OF ERGONOMIC GYMNASTICS AND THE ADMINISTRATION OF TOMATO JUICE IN PATIENTS WITH HYPERCHOLESTEROLEMIA - SUNARTI, NINA; FATIMAH, SITI; WULAN SARI, INDAH MEI (Jurnal Afiat : Kesehatan dan Anak, 2025)
Background: Hypercholesterolemia is a blood fat disorder where cholesterol levels in the blood exceed 200 mg/dL from normal levels. The prevalence of Hypercholesterolemia sufferers in Tugu Utara Village, Koja District, North Jakarta is still high, this is due to lifestyle (diet and smoking). Therefore, it is necessary to provide health education about Hypercholesterolemia and also non-pharmacological therapy by doing ergonomic gymnastics and giving tomato juice. Research Objective: To improve effective health management in Hypercholesterolemia patients in Tugu Utara Village, Koja District, North Jakarta. Data collection was carried out using instruments, interview techniques, observations, physical examinations and documentation studies. Results: From the results of the study conducted on 3 fostered patients, namely by providing health education, providing non-pharmacological therapy in the form of ergonomic exercises for 20 minutes and consuming tomato juice 1x/day. It is found that the change in cholesterol levels in the blood decreases. Tip: Hypercholesterolemia can be prevented as early as possible by making regular lifestyle changes, diet, exercise and control.